Pemberdayaan Guru SD/MI Melalui Peningkatan Kualitas Pembelajaran Matematika (Dinamis: Jurnal Pengabdian Kepada Masyarakat, 2021)
This activity aims to provide basic knowledge about learning mathematics how to use media and several learning models, one of which is RME, as well as knowledge about the 2013 curriculum. math. To increase the basic knowledge of mathematics learning, the trainees were given basic knowledge and skills on: 1) Mathematics Learning Problems at SD/MI Level, 2) Elementary Mathematics Textbooks according to the 2013 Curriculum, 3) RME, 4) Fun Mathematics Learning Methods. The service was held at SDI Makarimul Akhlak Building with ±30 participants on Saturday, May 14-19 2016. The methods used were lecture, practice, question and answer, discussion and practice methods. Based on the results of the evaluation, it turned out that in general there was an increase in the knowledge of the training participants for the empowerment of SD/MI teachers in improving mathematics learning, this was evidenced by the tasks given to the participants. In the future, the hope of this activity is that participants can practice in class during math lessons and can transfer the knowledge that has been obtained to other SD/MI teachers.